POLITIK HUKUM OTONOMI DAERAH TENTANG PEMILUKADA - Eko Sabar Prihatin (Masalah-Masalah Hukum, 2014)
Legal policy as the direction of the national legal system should provide guidance on how policies on particular issues of regional autonomy election conducted by the organizers of the central government to lower governmental units. The need for the role of local government is strengthened by an understanding of the welfare state paradigm, requiring the intervention of the state in all areas of public life.